Beta-arrestin Biased Agonism/Antagonism at Cardiovascular Seven Transmembrane-spanning Receptors - Lymperopoulos, Anastasios (Current Pharmaceutical Design, 2012)
Heptahelical, G protein-coupled or seven transmembrane-spanning receptors, such as the β-adrenergic and the angiotensin II type 1 receptors, are the most diverse and therapeutically important family of receptors in the human genome, playing major roles in the physiology of various organs/tissues including the heart and blood vessels. Ligand binding activates heterotrimeric G proteins that transmit intracellular signals by regulating effector enzymes or ion channels. G protein signaling is terminated, in large part, by phosphorylation of the agonist-bound receptor by the G-protein coupled receptor kinases (GRKs), followed by βarrestin binding, which uncouples the phosphorylated receptor from the G protein and subsequently targets the receptor for internalization. As the receptor-βarrestin complex enters the cell, βarrestin-1 and -2, the two mammalian βarrestin isoforms, serve as ligand-regulated scaffolds that recruit a host of intracellular proteins and signal transducers, thus promoting their own wave of signal transduction independently of G-proteins. A constantly increasing number of studies over the past several years have begun to uncover specific roles played by these ubiquitously expressed receptor adapter proteins in signal transduction of several important heptahelical receptors regulating the physiology of various organs/ systems, including the cardiovascular (CV) system. Thus, βarrestin-dependent signaling has increasingly been implicated in CV physiology and pathology, presenting several exciting opportunities for therapeutic intervention in the treatment of CV disorders. Additionally, the discovery of this novel mode of heptahelical receptor signaling via βarrestins has prompted a revision of classical pharmacological concepts such as receptor agonism/antagonism, as well as introduction of new terms such as “biased signaling”, which refers to ligand-specific activation of selective signal transduction pathways by the very same receptor. The present review gives an overview of the current knowledge in the field of βarrestin-dependent signaling, with a specific focus on CV heptahelical receptor βarrestin-mediated signaling and on “biased” CV heptahelical receptor ligands that promote or inhibit it. Exciting new possibilities for cardiovascular therapeutics arising from the delineation of this βarrestin-dependent signaling are also discussed.
Keywords: angiotensin II type 1 receptor